Otolith-based age and growth of the Lessepsian species Fistularia commersonii (Osteichtyes: Fistulariidae) in South of Sicily (Central Mediterranean Sea). Issue 4 (1st October 2016) - Vitale, S.; Arculeo, M.; Vaz, A.; Giusto, G. B.; Gancitano, S.; Ragonese, S.
Abstract: During spring–summer 2013, 23 specimens of the Lessepsian Fistularia commersonii Rüppell, 1838 were studied through occasional catches by artisanal and coastal trawler fisheries in the South of Sicily (Mediterranean Sea). The total lengths (TL, cm, without filament) and weight (W, g) ranged between 69.0 and 104.0 cm and 155 and 798 g, respectively. The estimated sex-combined parameters of the length–weight relationship (k = 9*10 –9 ; b = 3.6) suggested a positive allometry. All pairs of sagittae were examined under a stereomicroscope and the age estimated by counting the complete translucent zones, both as whole and thin sections, with ages from 3 to 5 years. Growth parameters (von Bertalanffy Growth Function: L∞ = 101.4; K = 0.52; A0 = 0) were similar to those reported in the literature using vertebra readings. Some conceptual aspects were taken into account in the potential differences in growth rate between the nowadays-established Mediterranean specimens and the native Indo–Pacific ones.